РОЗВИТОК ОСВІТ И ЯК СУСПІЛ ЬНОЇ ЦІ ННОСТІ : ІСТОРИКО- ФІЛ ОСОФСЬКИЙ ДИСКУРС - Dzvinchuk, D (Continuing Professional Education: Theory and Practice, 2019)
The sources of the education as the social value are analyzed in the article; the role of the education and written language in the appearance and development of the agrarian society is conceived; the centers of the writing and the basis of sciences formation are observed; it was found out that the education and writing were the highest achievements of the human intelligence and played the unique and important social role, that rose more and more in the approximation to the present